Rapid Maxillary Expansion Has a Beneficial Effect on the Ventilation in Children With Nasal Septal Deviation: A Computational Fluid Dynamics Study - Chen, Shuai; Wang, Jingying; Xi, Xun; Zhao, Yi; Liu, Hong; Liu, Dongxu (Frontiers in Pediatrics, 2022)
Nasal septal deviation (NSD) is one of the most common nasal diseases. Different from common clinical examination methods, computational fluid dynamics (CFD) can provide visual flow information of the nasal cavity. The dimension and volume of the nasal cavity are easily affected by the rapid maxillary expansion (RME). The purpose of this study is to use CFD to evaluate the effect of RME on the aerodynamics of the nasal cavity in children with maxillary transverse deficiency and NSD. CFD was implemented after 3D reconstruction based on the CBCT of 15 children who have completed RME treatment. After treatment, the volume increase of nasal cavity, nasopharynx, oropharynx and pharynx was not statistically significant. Wall shear stress of nasal cavity after RME, 1.743  0.709 Pa, was significantly lower than that before RME, 2.684  1.073 Pa. Meanwhile, the maximal negative pressure in the pharyngeal airway during inspiration was smaller after RME (−31.176 Pa) than before (−48.144Pa). This study suggested that RME has a beneficial effect on the nasal ventilation. The nasal airflow became more symmetrical in bilateral nasal cavity after RME. The pharyngeal resistance decreased with the reduction of nasal resistance and the increase in the volume of oropharynx after RME.